Pemodelan Regresi Spline pada Studi Kasus Angka Kematian Bayi di Jawa Timur Tahun 2015 - Maria Fatima O L (J STATISTIKA: Jurnal Imiah Teori dan Aplikasi Statistika, 2018)
The question facing the East Java province in the field of health is maternal mortality (AKI) and infant mortality (AKB) which has decreased slowly. With regard to the target of the Millennium Development Goals (MDGs) in 2015 to AKB is the 23 deaths per 1.000 live births. AKB in East Java province, according to the Central Bureau of statistics (BPS) in 2015 i.e. amounting to 24 deaths per 1.000 live births. Based on the high degree of AKB in East Java the year 2015 then regression splines method applied to analyze AKB and the factors that affected it. Analysis of the results obtained that the linear relationship between the precise model of the percentage of labor by non medical personnel against infant mortality in East Java the year 2015 with 1 point of knots based on Generalized Cross Validation (GCV) a minimum of 39.22079. Based on the results of the analysis also obtained the best model Multivariable linear splines are linear splines with 1 point of knots based on Generalized Cross Validation (GCV) a minimum of 34.11737. Variables that influence significantly taking action against infant mortality in East Java the year 2015 are: the percentage of women who are the age of the first marriage of less than 17 years and the percentage of women who never school/did not finish ELEMENTARY SCHOOL. Persoalan yang dihadapi Provinsi Jawa Timur dalam bidang kesehatan adalah angka kematian ibu (AKI) dan angka kematian bayi (AKB) yang mengalami penurunan secara lambat. Berkaitan dengan target Millenium Development Goals (MDGs) tahun 2015 untuk AKB adalah 23 kematian per 1.000 kelahiran hidup. AKB di Provinsi Jawa Timur menurut Badan Pusat Statistik (BPS) pada tahun 2015 yakni sebesar 24 kematian per 1.000 kelahiran hidup. Berdasarkan tingginya AKB di Jawa Timur tahun 2015 maka metode regresi spline diterapkan untuk mengkaji AKB dan faktor-faktor yang mempengaruhinya. Dari hasil analisis didapatkan bahwa model spline linear hubungan antara persentase persalinan oleh tenaga non medis terhadap angka kematian bayi di Jawa Timur tahun 2015 dengan satu titik knot berdasarkan Generalized Cross Validation (GCV) minimum sebesar 39,22079. Berdasarkan hasil analisis juga didapatkan model spline linear multivariabel terbaik adalah spline linear dengan satu titik knot berdasarkan Generalized Cross Validation (GCV) minimum sebesar 34,11737. Variabel yang berpengaruh signifikan tehadap angka kematian bayi di Jawa Timur tahun 2015 adalah : persentase perempuan yang usia perkawinan pertama kurang dari 17 tahun dan persentase wanita yang tidak pernah sekolah/tidak tamat SD.